LPTO-02. INTRATHECAL (IT) TRASTUZUMAB (T) FOR THE TREATMENT OF LEPTOMENINGEAL DISEASE (LM) IN PATIENTS (PTS) WITH HUMAN EPIDERMAL RECEPTOR-2 POSITIVE (HER2+) CANCER: A MULTICENTER PHASE 1/2 STUDY. (12th August 2019) - Kumthekar, Priya; Lassman, Andrew B; Lin, Nancy; Grimm, Sean; Gradishar, William; Pentsova, Elena; Jeyapalan, Suriya; Groves, Morris; Melisko, Melissa; Raizer, Jeffrey
Abstract: Patients with HER2+ breast cancer have frequent LM. A multi center phase 1/2 study assessing safety and efficacy of IT T in LM patients was conducted. The primary endpoint in Phase 2 was response rate (RR). Complete response (CR) required cytologic CR (CCR) + radiographic CR (RCR) + stable clinical function. Partial response (PR) required either CCR with stable/improved imaging or RCR with stable cytology + stable/improved clinical symptoms. Pts received IT T via intraventricular Ommaya reservoir. Phase 1 dosing started at 10 mg, then increasing by 20 mg up to 80 mg. Each cycle (C) was 4 weeks with 2x treatment/week in C1, weekly in C2, and every two weeks after C2. Pts were allowed to continue on hormonal agents if systemic disease was controlled at the time of LM development. Concurrent radiation therapy was not allowed unless exceptionally needed locally for pain control. 34 pts were enrolled with 26 its in the phase 2. The median age was 51 (25–69). IT T was well tolerated with no DLTs seen throughout; determined MTD was 80 mg for phase 2. All patients treated in the Phase 2 had HER2+ breast cancer, 2 patients in the Phase 1 had non-breast histologies. Median cycles completed was 2 (1–22). Median follow up was 9.1 months (0.4- 28.9). In Phase 2, 5 pts (19.2%) had PR, 13 (50%) had SD, and 8 (30.8%) had PD. For Phase 2 pts, median PFS was 2.4 months (CI 1.0–5.5) and median OS was 12.1 months (CI 4.3–19.6) IT T was well tolerated up to a dose of 80 mg. Primary endpoint of 25% RR was not met, however 69% had clinical benefit (stable disease or better). Median OS exceeded historical controls. Future studies are warranted to evaluate IT T in HER2+ LM.